Lessons from silage adoption studies in Honduras - Reiber, Christoph; Schultze-Kraft, Rainer; Peters, Michael; Hoffmann, Vivian (2013)
To date, silage adoption has been low in the tropics, particularly under smallholder conditions. Innovation and adoption processes of silage technologies were promoted in drought-constrained areas of Honduras using a flexible, site-specific and participatory research and extension approach. A total of about 250 farmers participated in training workshops and field days conducted in 13 locations. Smallholders successfully ensiled maize, sorghum and/or Pennisetum spp., mainly in heap and earth silos, while adoption of little bag silage (LBS) was low. LBS proved useful as a demonstration, experimentation and learning tool. A ‘silage boom’ occurred in 5 locations, where favorable adoption conditions included the presence of demonstration farms and involvement of key innovators, lack of alternative dry season feeds, perceived benefits of silage feeding, a favorable milk market and both extension continuity and intensity. The lack of chopping equipment was the main reason for non-adoption by poor smallholders. The study showed that, when targeting production system needs and farmer demands, silage promotion can lead to significant adoption, including at smallholder level, in the tropics. This experience could contribute to an increase in effectiveness and sustainability of silage extension in similar situations elsewhere.